Negative electrode slurry for lithium-ion secondary battery, method for producing negative electrode for lithium-ion secondary battery, method for producing lithium-ion secondary battery, negative electrode for lithium-ion secondary battery, and lithium-ion secondary battery

CN116868364BActive Publication Date: 2026-10-16PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202180093338.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-02-18
Filing Date
2021-12-21
Publication Date
2026-10-16
Estimated Expiration
2041-12-21

AI Technical Summary

Benefits of technology

[0021] According to one aspect of the present disclosure, a negative electrode slurry for lithium-ion secondary batteries can suppress the decrease in viscosity over time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004384574630000021
    Figure BDA0004384574630000021
  • Figure BDA0004384574630000031
    Figure BDA0004384574630000031
  • Figure BDA0004384574630000041
    Figure BDA0004384574630000041
Patent Text Reader

Abstract

A negative electrode slurry for a lithium-ion secondary battery of one embodiment of the present disclosure includes a negative electrode active material, a thickening material, a preservative component, and a solvent. The thickening material includes carboxymethyl cellulose or a salt thereof. The solvent includes water. The preservative component includes a cyclic hydroxamic acid ethanolamine salt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to: negative electrode slurry for lithium-ion secondary batteries, a method for manufacturing a negative electrode for lithium-ion secondary batteries, a method for manufacturing lithium-ion secondary batteries, a negative electrode for lithium-ion secondary batteries, and lithium-ion secondary batteries. Background Technology

[0002] From the perspectives of ease of solvent recovery after coating / drying of the negative electrode current collector and environmental considerations, it is desirable to use water as the solvent in the negative electrode slurry for lithium-ion secondary batteries. Furthermore, it is known in the past to add a thickening material containing carboxymethyl cellulose salt to the negative electrode slurry for lithium-ion secondary batteries to achieve dispersion stabilization of the negative electrode active material in the solvent / prevent sedimentation (see, for example, Patent Document 1).

[0003] Existing technical documents

[0004] Patent documents

[0005] Patent Document 1: Japanese Patent Application Publication No. 05-074461 Summary of the Invention

[0006] The problem the invention aims to solve

[0007] However, when water is used as a solvent and carboxymethyl cellulose or its salts are used as a thickening material, the viscosity of the negative electrode slurry for lithium-ion secondary batteries decreases over time due to the decomposition of carboxymethyl cellulose or its salts by microorganisms contained in the water. As a result, the negative electrode active material dispersed in the slurry becomes prone to sedimentation.

[0008] Therefore, when using a negative electrode slurry for lithium-ion secondary batteries containing water and carboxymethyl cellulose or its salts, the negative electrode active material may settle during the storage of the slurry or during the manufacturing process of the negative electrode. Thus, there is a concern that uneven coating and reduced battery performance may occur when the slurry is coated onto the negative electrode current collector, for example.

[0009] Therefore, the object of this disclosure is to provide a negative electrode slurry for lithium-ion secondary batteries with suppressed viscosity reduction over time. Furthermore, the object of this disclosure is to provide a negative electrode for lithium-ion secondary batteries using this negative electrode slurry and a method for manufacturing a lithium-ion secondary battery.

[0010] Solution for solving the problem

[0011] The negative electrode slurry for lithium-ion secondary batteries disclosed herein is characterized by comprising: a negative electrode active material, a thickening material, a corrosion inhibitor, and a solvent, wherein the thickening material comprises carboxymethyl cellulose or a salt thereof, the solvent comprises water, and the corrosion inhibitor comprises a cyclic oxime ethanolamine salt as shown in formula (1).

[0012]

[0013] (In formula (1), R1 and R2 are each independently hydrogen atoms or optional hydrocarbon groups with substituents).

[0014] The method for manufacturing a negative electrode for a lithium-ion secondary battery disclosed herein is characterized by comprising the following step: coating a negative electrode slurry for a lithium-ion secondary battery onto a negative electrode current collector.

[0015] The method for manufacturing a lithium-ion secondary battery according to one aspect of this disclosure is characterized in that a negative electrode for a lithium-ion secondary battery is obtained by the aforementioned method for manufacturing a negative electrode for a lithium-ion secondary battery.

[0016] The negative electrode for a lithium-ion secondary battery according to one aspect of this disclosure is characterized by having a negative electrode composite material layer, the negative electrode composite material layer comprising: a negative electrode active material, a thickening material, and a corrosion inhibitor, wherein the thickening material comprises carboxymethyl cellulose or a salt thereof, and the corrosion inhibitor comprises a cyclic oxime ethanolamine salt as shown in the following formula (1).

[0017]

[0018] (In formula (1), R1 and R2 are each independently hydrogen atoms or optional hydrocarbon groups with substituents).

[0019] The lithium-ion secondary battery of this disclosure is characterized by having the aforementioned negative electrode for a non-aqueous electrolyte secondary battery.

[0020] The effects of the invention

[0021] According to one aspect of the present disclosure, a negative electrode slurry for lithium-ion secondary batteries can suppress the decrease in viscosity over time. Attached Figure Description

[0022] Figure 1 This is a cross-sectional view of a lithium-ion secondary battery as an example of an implementation.

[0023] Figure 2 The graph shows the viscosity of the negative electrode slurry of Examples 1-4 and the comparative example over time.

[0024] Figure 3 The graph shows the change in viscosity retention over time of the negative electrode slurry of Examples 1-4 and the comparative examples. Detailed Implementation

[0025] (Negative electrode slurry for lithium-ion secondary batteries)

[0026] The negative electrode slurry for lithium-ion secondary batteries (hereinafter, sometimes referred to as negative electrode slurry) of this embodiment includes: a negative electrode active material, a thickening material, a corrosion inhibitor, and a solvent.

[0027] As a negative electrode active material, there are no particular limitations on the materials that can be used as negative electrode active materials in conventional lithium-ion secondary batteries. Examples include carbon materials such as artificial graphite, natural graphite, hard carbon, soft carbon, carbon nanotubes, and activated carbon; metals such as Li, Si, and Sn; alloys; metal oxides; metal sulfides; and metal nitrides. As alloys, examples include Li-containing alloys such as lithium-aluminum alloys, lithium-tin alloys, lithium-lead alloys, and lithium-silicon alloys. Furthermore, as metal oxides, examples include lithium titanate (Li₄Ti₅O₂). 12 Examples include (e.g.), cobalt oxide, iron oxide, etc. Additionally, examples of metal nitrides include lithium-containing nitrides such as lithium cobalt nitride, lithium iron nitride, and lithium manganese nitride. Furthermore, chalcogenide compounds can also be cited as examples.

[0028] Thickening materials are used to adjust the negative electrode slurry to a suitable viscosity range and include carboxymethyl cellulose or its salts (hereinafter, sometimes referred to as CMC or CMC salts). It should be noted that the thickener may contain either CMC or a CMC salt, or both. Examples of CMC salts include ammonium salts, sodium salts, potassium salts, and lithium salts. The negative electrode slurry of this embodiment may contain conventionally known thickening materials such as polyethylene glycol and polyethylene oxide, along with CMC or CMC salts.

[0029] The content of CMC or CMC salt relative to the total amount of negative electrode slurry can, for example, range from 0.5% to 3% by mass.

[0030] The solvent includes water. From the perspectives of ease of recovery during drying and environmental suitability, it is desirable for the solvent to consist solely of water, but it may also include water-soluble organic solvents such as alcohols. The water is not specifically limited to ultrapure water, pure water, or industrial water, but if a grade with no restrictions on treatment costs or usage is chosen, Japanese Industrial Standard A1 is typically used.

[0031] The preservative component comprises a cyclic oxime ethanolamine salt as shown in the following formula (1).

[0032]

[0033] In formula (1), R1 and R2 are each independently hydrogen atoms or optional hydrocarbon groups with substituents.

[0034] In the formula, R1 can be optionally a substituent hydrocarbon group, for example, a straight-chain or branched alkyl or alkenyl group, an optionally straight-chain or branched cycloalkyl or aryl group, or an alkylepoxyalkyl group (the alkyl and alkylene sites in the group can be straight-chain or branched). The number of carbon atoms in the optionally substituent hydrocarbon group of R1 can be, for example, 1 or more, 3 or more, or 6 or more, and can also be 30 or less, 20 or less, or 8 or less.

[0035] In the formula, R2 can be optionally a substituent hydrocarbon group, for example, a straight-chain or branched alkyl or alkenyl group, an optionally straight-chain or branched cycloalkyl group, a phenyl group, or a benzyl group. The number of carbon atoms in the optionally substituent hydrocarbon group of R2 can be, for example, 1 or more, or 6 or less, or 4 or less. As a specific example of R2, it can be methyl.

[0036] Specific examples of cyclic oxime acid ethanolamine salts include pyridone ethanolamine salts (1-hydroxy-4-methyl-6-(2,4,4-trimethylpentyl)-2(1H)-pyridone ethanolamine salt) as shown in formula (1A) below, and cyclopyridone ethanolamine salts (6-cyclohexyl-1-hydroxy-4-methyl-2(1H)-pyridone ethanolamine salt) as shown in formula (1B) below. Either one or both can be used.

[0037]

[0038] Conventionally, in negative electrode slurries containing CMC or CMC salt and water, microorganisms such as bacteria in the water secrete cellulase to decompose the CMC or CMC salt. Therefore, the viscosity of the negative electrode slurry decreases over time, and the negative electrode active material in the slurry settles. However, the negative electrode slurry of this embodiment, using the cyclic oxime acid ethanolamine salt shown in the above-described formula (1), can inhibit the growth of bacteria and other microorganisms, or cause the microorganisms to die. Therefore, the viscosity decrease of the negative electrode slurry over time is suppressed. As a result, the settling of the negative electrode active material in the negative electrode slurry is suppressed. For example, uneven coating when the slurry is coated onto the negative electrode current collector can be suppressed, and further, the degradation of battery performance can be suppressed.

[0039] Regarding the content of the aforementioned cyclic oxime ethanolamine, in order to effectively suppress the viscosity reduction of the negative electrode slurry over time, it is preferably 0.025% by mass or more relative to the total amount of the negative electrode slurry. It should be noted that there is no particular upper limit; for example, the content of cyclic oxime ethanolamine relative to the total amount of the negative electrode slurry can be less than 1% by mass.

[0040] In addition to the negative electrode active material, thickener, preservative, and solvent, the negative electrode slurry of this embodiment may also include additives such as binders. Examples of binders include polyethylene, polypropylene, fluorinated binders, rubber particles, acrylic polymers, and vinyl polymers. Examples of fluorinated binders include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), and vinylidene fluoride-hexafluoropropylene copolymer. Examples of rubber particles include acrylate rubber particles, styrene-butadiene rubber (SBR) particles, and acrylonitrile rubber particles.

[0041] Regarding the viscosity of the negative electrode slurry, from the perspective of suppressing the sedimentation of the negative electrode active material, it can be above 2000 mPa·s or above 5000 mPa·s. However, if the viscosity of the negative electrode slurry is too high, it becomes difficult to uniformly coat it to the required thickness. Therefore, the viscosity can be below 20000 mPa·s or below 15000 mPa·s. The viscosity of the negative electrode slurry was measured using a BM rotational viscometer at 25°C, at a rotation speed of 20 rpm, and after the rotor had rotated for 1 minute.

[0042] The preparation of negative electrode slurry can be carried out using various known methods. For example, various materials such as negative electrode active material, thickener, and preservatives can be dispersed in a solvent using commercially available dispersion devices. Specific examples of dispersion devices include media-based dispersers such as bead mills, ball mills, planetary ball mills, kneaders, planetary mixers, and dispersion mixers, as well as media-free dispersers such as homogenizers.

[0043] (Negative electrode for lithium-ion secondary batteries)

[0044] When fabricating the negative electrode using the negative electrode slurry of this embodiment, the same method as in the past can be employed. For example, the negative electrode slurry of this embodiment is coated onto the negative electrode current collector and dried to form a negative electrode composite material layer, which is then further calendered as needed to obtain the negative electrode. The negative electrode composite material layer can be formed on both sides of the negative electrode current collector in the thickness direction. The thickness of the negative electrode composite material layer is, for example, 20 to 150 μm when formed on one side of the negative electrode current collector, and for example, 50 to 250 μm in total when formed on both sides of the negative electrode current collector.

[0045] As a negative electrode current collector, commonly used in the field of lithium-ion secondary batteries, such as sheets and foils containing copper, nickel, or other precious metals, can be used. The sheets can be porous. Porous materials include, for example, foamed materials, woven fabrics, and non-woven fabrics. The thickness of the sheets and foils is not particularly limited, for example, from 1 to 100 μm.

[0046] The negative electrode slurry can be applied to the surface of the negative electrode current collector using methods such as slot die coaters, reverse roller coaters, lip coaters, scraper coaters, blade coaters, gravure coaters, and dip coaters. The negative electrode slurry applied to the negative electrode current collector can be dried close to natural drying, but for productivity reasons, drying at 100°C to 200°C for 10 minutes to 1 hour is desirable.

[0047] When a negative electrode composite layer is formed by heating and drying the negative electrode slurry, thermally denatured substances produced by the thermal denaturation of the aforementioned cyclic oxime acid ethanolamine salt in the negative electrode slurry are sometimes detected in the negative electrode composite layer. For example, when pyridone ethanolamine salt is used as the cyclic oxime acid ethanolamine, in addition to pyridone ethanolamine salt in the negative electrode composite layer, thermally denatured substances such as those shown in formulas (2) to (4) are sometimes also detected.

[0048]

[0049] Calendering, for example, is performed multiple times using a roll press at a specified linear pressure until the negative electrode reaches a specified thickness.

[0050] After this series of processes, the material is cut and processed to obtain a negative electrode for lithium-ion secondary batteries. In the negative electrode for lithium-ion secondary batteries of this embodiment, the content of the above-mentioned cyclic oxime ethanolamine is preferably 0.05% by mass or more relative to the total amount of the negative electrode composite material layer.

[0051] (Lithium-ion secondary battery)

[0052] The lithium-ion secondary battery of this embodiment utilizes a negative electrode made using the negative electrode slurry of this embodiment. Otherwise, it can adopt the same structure as conventional lithium-ion secondary batteries.

[0053] Figure 1 This is a cross-sectional view of a lithium-ion secondary battery as an example of an implementation. Figure 1 The lithium-ion secondary battery 10 shown includes: a wound electrode body 14 formed by winding a positive electrode 11 and a negative electrode 12 with a separator 13, an electrolyte, insulating plates 18 and 19 respectively disposed above and below the electrode body 14, and a battery casing 15 for housing the above components. The battery casing 15 is composed of a bottomed cylindrical casing body 16 and a sealing body 17 that blocks the opening of the casing body 16. It should be noted that other forms of electrode bodies, such as a stacked electrode body in which the positive and negative electrodes are alternately stacked with a separator, can be used instead of the wound electrode body 14. In addition, examples of battery casing 15 include cylindrical, square, coin-shaped, button-shaped, etc., metal casings, and resin casings formed by laminating resin sheets (laminated batteries).

[0054] The outer casing 16 is, for example, a bottomed cylindrical metal container. A gasket 28 is provided between the outer casing 16 and the sealing body 17 to ensure the airtightness of the battery interior. The outer casing 16 has, for example, a bulge 22 that protrudes inward from a portion of its side surface to support the sealing body 17. The bulge 22 is preferably formed in a ring shape along the circumference of the outer casing 16, and its upper surface supports the sealing body 17.

[0055] The sealing body 17 has a structure consisting of a metal plate 23 with partial openings stacked from the electrode body 14 side, a lower valve body 24, an insulating member 25, an upper valve body 26, and a cover 27. Each component constituting the sealing body 17 has, for example, a circular or annular shape, and all components except the insulating member 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected to each other at their respective central portions, and the insulating member 25 is sandwiched between their respective peripheral portions. When the internal pressure of the secondary battery 10 rises due to heat generated by internal short circuits, for example, the lower valve body 24 deforms and breaks in a manner that pushes the upper valve body 26 into the cover 27 side, blocking the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure rises further, the upper valve body 26 breaks, and gas is discharged from the opening of the cover 27.

[0056] Figure 1 In the lithium-ion secondary battery 10 shown, the positive electrode lead 20, mounted on the positive electrode 11, extends towards the sealing body 17 through the through hole in the insulating plate 18, and the negative electrode lead 21, mounted on the negative electrode 12, extends towards the bottom of the outer casing 16 through the outer side of the insulating plate 19. The positive electrode lead 20 is connected by welding or the like to the lower surface of a metal plate 23, which serves as a partial opening in the bottom plate of the sealing body 17. The top plate of the sealing body 17, i.e., the cover 27, which is electrically connected to the partially opening metal plate 23, becomes the positive terminal. The negative electrode lead 21 is connected by welding or the like to the inner bottom surface of the outer casing 16, making the outer casing 16 the negative terminal.

[0057] The following is a detailed description of the positive electrode 11, the negative electrode 12, the separator 13, and the electrolyte.

[0058] The negative electrode 12 is a negative electrode obtained by the negative electrode slurry manufacturing method of this embodiment. The structure of the negative electrode 12 is as described above, and the description is omitted here.

[0059] The positive electrode 11 can be manufactured as follows: a positive electrode slurry is coated on one or both sides of the positive electrode current collector and dried, then calendered to form a positive electrode composite material layer. Commonly used positive electrode current collectors in the field of lithium-ion secondary batteries can be used, such as sheets or foils containing stainless steel, aluminum, aluminum alloys, titanium, etc. The sheet can be a porous body. Porous bodies may contain, for example, foamed materials, woven fabrics, non-woven fabrics, etc. The thickness of the sheet and foil is not particularly limited, for example, from 1 to 500 μm.

[0060] Positive electrode slurry can contain known positive electrode active materials, conductive materials, binder materials, thickeners, dispersion media, etc.

[0061] Examples of positive electrode active materials include olivine-type lithium salts such as LiFePO4, chalcogenide compounds such as titanium disulfide and molybdenum disulfide, manganese dioxide, and conventional lithium-containing composite metal oxides. Conventional lithium-containing composite metal oxides are, for example, metal oxides containing lithium and a transition metal, or metal oxides in which a portion of the transition metal is replaced by a different element. Examples of different elements include Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, and B, with Mn, Al, Co, Ni, and Mg being preferred. There may be one or more different different elements.

[0062] As a specific example of lithium-containing composite metal oxides, Li can be cited as an example. x CoO2, Li x NiO2, Li x MnO2, Li x Co y Ni 1-y O2, Li x Co y M 1-y O z Li x Ni 1-y M y O z Li x Mn2O4, Li x Mn 2-y M y O4, LiMPO4, Li2MPO4F (in each formula, M represents, for example, at least one element selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, V, and B. x = 0–1.2, y = 0–0.9, z = 2.0–2.3.) etc.

[0063] Examples of conductive materials include carbon black, graphite, carbon fiber, and metal fiber. Examples of carbon black include acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal cracking black. Conductive materials can be used alone or in combination of two or more.

[0064] As a bonding material, it can be used without particular limitation as long as it can be dissolved or dispersed in a dispersion medium. Examples include polyethylene, polypropylene, fluorinated bonding materials, rubber granules, acrylic polymers, and vinyl polymers. Examples of fluorinated bonding materials include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), and vinylidene fluoride-hexafluoropropylene copolymer. A single bonding material can be used alone, or in combination of two or more materials.

[0065] As a thickening material, commonly used materials in this field can be used, such as carboxymethyl cellulose or its salts.

[0066] The dispersion medium is preferably an amide such as N,N-dimethylformamide, dimethylacetamide, methylformamide, hexamethylphosphoramide, tetramethylurea, N-methyl-2-pyrrolidone (NMP), dimethylamine, methyl ethyl ketone, acetone, cyclohexanone, tetrahydrofuran, dimethyl sulfoxide, etc.

[0067] To prepare the positive electrode slurry, methods commonly used in this field can be employed. For example, the following methods can be used: mixing the above components using mixing devices such as planetary mixers, dispersion mixers, pin mills, kneaders, and homogenizers. The mixing devices can be used individually or in combination of two or more.

[0068] The positive electrode paste can be applied to the surface of the positive electrode current collector using, for example, a slot die coater, a reverse roller coater, a lip coater, a scraper coater, a doctor blade coater, a gravure coater, and an dip coater. The positive electrode composite paste applied to the positive electrode current collector is preferably dried close to natural drying, but for productivity reasons, drying at a temperature of 70°C to 200°C for 10 minutes to 5 hours is preferred.

[0069] The calendering process is carried out multiple times using a roller press at a specified linear pressure until the positive electrode 11 reaches the specified thickness.

[0070] After this series of processes, the cathode 11 is obtained through cutting and processing.

[0071] The separator 13 may be a microporous membrane formed of a polymer material. Examples of polymer materials include polyethylene, polypropylene, polyvinylidene fluoride, polyvinylidene chloride, polyacrylonitrile, polyacrylamide, polytetrafluoroethylene, polysulfone, polyethersulfone, polycarbonate, polyamide, polyimide, polyether (ethylene oxide, propylene oxide), cellulose (carboxymethyl cellulose, hydroxypropyl cellulose), poly(meth)acrylic acid, and poly(meth)acrylate. These polymer materials may be used alone or in combination of two or more. Alternatively, multilayer films with these microporous membranes overlapping may also be used. The thickness of the microporous membrane is, for example, 15 μm to 30 μm.

[0072] Electrolytes may include, for example, non-aqueous solvents and electrolyte salts. Electrolytes are not limited to liquid electrolytes; they may also be solid electrolytes that utilize gel polymers or the like.

[0073] Examples of non-aqueous solvents include cyclic carbonates and chain carbonates. Examples of cyclic carbonates include ethylene carbonate, propylene carbonate, and butyl carbonate. Examples of chain carbonates include dimethyl carbonate, diethyl carbonate, and methyl ethyl carbonate.

[0074] Examples of electrolyte salts include LiPF6, LiBF4, LiClO4, LiAsF6, LiCF3SO3, LiN(SO2CF3)2, LiN(SO2C2F5)2, and LiC(SO2CF3)3. These electrolyte salts can be used individually or in combination of two or more.

[0075] Example

[0076] The present disclosure will be further described below with reference to embodiments, but the present disclosure is not limited to these embodiments.

[0077] (Example 1)

[0078] Add 49.575% by mass of graphite powder as the negative electrode active material, 0.4% by mass of sodium carboxymethyl cellulose as a thickener, and 0.025 parts by mass of pyridone ethanolamine salt to 50% by mass water. Stir the mixture in a planetary mixer for 1 hour to obtain a negative electrode slurry. Add 1% by mass of bacterial solution to the negative electrode slurry to promote the growth of bacteria that produce enzymes that decompose CMC. Then, place the negative electrode slurry with added bacterial solution into a container with an inner diameter of 55 mm and a depth of 115 mm. While maintaining the temperature at 25 ± 0.2 °C in a constant temperature water bath, the viscosity change of the negative electrode slurry over time is confirmed using a BM rotational viscometer [Toki Sangyo Co., Ltd. "TVB-15M (trade name)"].

[0079] (Example 2)

[0080] The pyridone ethanolamine salt was replaced with ciclopirox olamine salt, and the negative electrode slurry was obtained in the same manner as in Example 1. Then, the viscosity change of the obtained negative electrode slurry over time was confirmed, as in Example 1.

[0081] (Example 3)

[0082] The amount of pyridone ethanolamine salt added was changed from 0.025% by mass to 0.01% by mass, and the amount of graphite powder was changed from 49.575% by mass to 49.59% by mass. Otherwise, the negative electrode slurry was obtained in the same manner as in Example 1. Then, the viscosity of the obtained negative electrode slurry over time was confirmed, as in Example 1.

[0083] (Example 4)

[0084] The pyridone ethanolamine salt was replaced with ciclopirox olamine salt, and the negative electrode slurry was obtained in the same manner as in Example 3. Then, the viscosity change of the obtained negative electrode slurry over time was confirmed in the same manner as in Example 1.

[0085] (Comparative Example)

[0086] Without adding pyridone ethanolamine salt, the negative electrode slurry was obtained in the same manner as in Example 1. Then, as in Example 1, the viscosity change of the obtained negative electrode slurry over time was confirmed.

[0087] Figure 2 To show the viscosity changes over time of the negative electrode slurry of Examples 1-4 and the comparative example, Figure 3 The graph shows the change in viscosity retention over time of the negative electrode slurry of Examples 1-4 and the comparative examples.

[0088] like Figure 2 and Figure 3 As shown, the viscosity of the negative electrode slurries in Examples 1, 2, and 4 remained essentially unchanged even after 168 hours from the time of slurry preparation. For the negative electrode slurry in Example 3, the viscosity decreased slowly after 30 hours from the time of slurry preparation, but compared with the negative electrode slurry of the comparative example without the addition of pyridone ethanolamine salt, the decrease in viscosity over time was suppressed.

[0089] Explanation of reference numerals in the attached figures

[0090] 10 Lithium-ion secondary battery, 11 Positive electrode, 12 Negative electrode, 13 Separator, 14 Electrode body, 15 Battery casing, 16 Casing body, 17 Sealing body, 18, 19 Insulating plate, 20 Positive electrode lead, 21 Negative electrode lead, 22 Bulges, 23 Partially open metal plate, 24 Lower valve body, 25 Insulating component, 26 Upper valve body, 27 Cover, 28 Gasket.

Claims

1. A negative electrode slurry for lithium-ion secondary batteries, comprising: a negative electrode active material, a thickening material, a corrosion inhibitor, and a solvent. The thickening material comprises carboxymethyl cellulose or its salt. The solvent contains water. The preservative component contains pyridone ethanolamine salt.

2. The negative electrode slurry for lithium-ion secondary batteries according to claim 1, wherein, The preservative also includes ciclopirox olamine salt.

3. The negative electrode slurry for lithium-ion secondary batteries according to claim 1 or 2, wherein, The content of the pyridone ethanolamine salt is 0.025% by mass or more relative to the total amount of the negative electrode slurry for lithium-ion secondary batteries.

4. A method for manufacturing a negative electrode for a lithium-ion secondary battery, comprising: The process of coating the negative electrode slurry of any one of claims 1 to 3 onto the negative electrode current collector.

5. A method for manufacturing a lithium-ion secondary battery, the method comprising manufacturing a lithium-ion secondary battery using a lithium-ion secondary battery negative electrode obtained by the method for manufacturing a lithium-ion secondary battery negative electrode according to claim 4.

6. A negative electrode for a lithium-ion secondary battery, comprising a negative electrode composite material layer, said negative electrode composite material layer comprising: a negative electrode active material, a thickening material, and an anti-corrosion component. The thickening material comprises carboxymethyl cellulose or its salt. The preservative component contains pyridone ethanolamine salt.

7. The negative electrode for a lithium-ion secondary battery according to claim 6, wherein, The preservative also includes ciclopirox olamine salt.

8. The negative electrode for a lithium-ion secondary battery according to claim 6 or 7, wherein, The content of the pyridone ethanolamine salt is more than 0.05% by mass relative to the total amount of the negative electrode composite material layer.

9. A lithium-ion secondary battery comprising a negative electrode for a lithium-ion secondary battery as described in any one of claims 6 to 8.

Citation Information

Patent Citations

  • Secondary battery negative electrode

    JP1993074461A

  • Lithium ion battery negative slurry and lithium ion battery

    CN101937983A

  • Negative electrode slurry for lithium ion secondary battery, negative electrode plate for lithium ion secondary battery and lithium ion secondary battery

    JP2013114959A

  • Immunosuppressant treatment for gastrointestinal diseases

    JP2020513280A